CRYSTAL CHEMISTRY OF MERCURY SULFOHALIDES OF COMPOSITION HG3S2HAL2 (HAL: CL, BR). I. CRYSTAL STRUCTURES OF TWO POLYMORPHIC MODIFICATIONS OF HG3S2CL2-XBRX (X ≈ 0.5) - Pervukhina N.V.; Magarill S.A.; Borisov S.V.; Naumov D.Yu.; Vasil'ev V.I. (My University, 2006)
Two polymorphic modifications of Hg3S2 Cl2-xBrx (x ≈ 0.5), have been prepared in attempts to synthesize lavrentievite, Hg3S2 (Cl,Br)2(Cl ≥ Br), a rare supergene suffohalide of mercury. The growth of single crystals from a gaseous phase was carried out at 540°C in an evacuated silica ampoule filled with a mixture of HgS (cinnabar), HgCl2 and HgBr2. We obtained bright yellow crystals of two phases, monoclinic (I) and cubic (II). The crystal structures of the two polymorphs, Hg2+3 S2Cl1.5Br0.5 (I) and Hg2+3S2Cl1.54 Br0.46 (II), have been determined by single-crystal X-ray-diffraction analysis. The structures were solved by direct methods and refined to an R of 0.0528 and 0.0282 using 1361 and 1026 unique observed reflections ( Fo > 4∑F) for compounds I and II, respectively. Compound I is monoclinic, C2/m, a 16,841(2), b 9.128(2), c 9.435(4) Å β 90.08(1)°, V 1450.3(7) Å, Z = 8 Compound II is cubic, Pm3n, a 18.0409(2) Å, V 5871.84(11) Å3, Z = 32. The Hg atoms are covalently bonded to two S atoms at 2.372(2)-2.484(2) Å [∠S-Hg-S 158.42(7)-180.0(0)°] and 2.386(3)-2.410(3)A[∠S-Hg-S 166.0(2)-176.1(2)°] for compounds I and 1I, respectively. Each S atom is bonded to three Hg atoms to form the SHg3 trigonal pyramids with the Hg-S-Hg angles of 93.06(8)-96.21(7)° and 95.4(1)-96.6(2)° for I and II, respectively. In compound I, the SHg3 fragments share the Hg vertices to form corrugated [Hg6S4]∞∞ layers. Within the layer, five of the six short Hg-S bonds form closed [Hg4S4] rings of two orientations, whereas the sixth Hg-S bond joins these rings together via the Hg-S-Hg bridges into a two-dimensional system. The halogen atoms are located within and in between the [Hg6X4]∞∞ layers. In compound II, the SHg3 fragments share the Hg vertices to form isolated sulfur cubes with edges centerred by the Hg atoms. The halogen ions are located both within and in between the [Hg12S8] cubes. Taking into account the halogen tons, the Hg atoms are in distortect octahedral coordination to anions.
Keywords: ARZAK MERCURY DEPOSIT; CHLORINE DOMINANCE; CRYSTAL STRUCTURE; KADYREL MERCURY DEPOSIT; LAVRENTIEVITE; MERCURY SULFOHALIDE; POLYMORPHISM; RUSSIA; TUVA